Marmura’nın Tanrı’nın Tikelleri Bilmesi Problemindeki Düşüncelerinin Analizi ve Eleştirisi - Akkanat, Hasan (Dinî araştırmalar, 2009)
Marmura critizes Alfarab and Avicenna in "Some Aspects of Avicenna’s Theory of God’s Knowledge of Particulars" and "Divine Omniscience and Future Contingents in Alfarabi and Avicenna" that he examined God’s knowledge of particulars as a problem of Islamic philosophy. Those critiques of his are generally on two points: Marmura’s first important critique is that in Avicenna’s theory, God knows only the celestial intellects individually and conceptually which are each the only member of its species. He also knows the corruptible or transient particulars by attributing it to the only member of its species. The descriptionof the second particular can be acquired conceptually by the first. His second important critique is that God in Avicenna’s philosophy knows particulars with some universal qualities. The universal qualities can’t specify the particular because it is one among the others that share these same qualities. So God apprehends those qualities belonging to one individual only without knowing them belon